Patient with Recurrent Hypoglycemia Caused by Malignant Giant Insulinoma - Clareza Arief Wardhana; Anak Agung Wiradewi Lestari; I Nyoman Wande (Indonesian Association of Clinical Pathologist and Medical laboratory, 2023)
Insulinoma is a functional endocrine tumor in the pancreas and the most common cause of hypoglycemia due to endogenic hyperinsulinism. Insulinoma is a rare case, with an incidence of 1-4 cases per million people each year. Malignant insulinoma is an insulinoma that is proven to metastasize to other tissues and only happens in 5-10% of insulinoma cases. Insulinoma with a size >9 cm is classified as giant insulinoma. Since 1927, fewer than 40 cases of giant insulinoma have been reported. 56 years old female was referred from a private hospital with the chief complaint of decreased consciousness due to recurrent hypoglycemia. On physical examination, palpable ±12x4 cm solid mass with an uneven surface in the epigastric region. Laboratory tests found an increase in c-peptide, fasting insulin, and liver function tests. A contrast CT scan found a heterogeneous solid mass 7.6x8.6x13.6 cm in cauda of the pancreas and hepatomegaly with multiple metastatic nodules. Results of pancreas and liver biopsy showed poorly differentiated carcinoma that metastasizes to the liver. In this case, based on patient history, physical and other examinations, it can be concluded that the patient was diagnosed with an observation of recurrent hypoglycemia caused by giant insulinoma with liver metastases.